2018
DOI: 10.1016/j.neubiorev.2018.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual multisensory integration in individuals with autism spectrum disorder: A systematic review and meta-analysis

Abstract: An ever-growing literature has aimed to determine how individuals with autism spectrum disorder (ASD) differ from their typically developing (TD) peers on measures of multisensory integration (MSI) and to ascertain the degree to which differences in MSI are associated with the broad range of symptoms associated with ASD. Findings, however, have been highly variable across the studies carried out to date. The present work systematically reviews and quantitatively synthesizes the large literature on audiovisual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 115 publications
9
123
2
Order By: Relevance
“…Our results suggest that a candidate core mechanism playing a role in BM processing anomalies in ASD is linked to the temporal properties of moving dots embedded in a PLD. This is consistent with several experimental pieces of evidence and theoretical proposals suggesting that one of the core anomaly of individuals with ASD is related to temporal binding of uni-and -multi-sensory information (Brock, Brown, Boucher, & Rippon, 2002;Feldman et al, 2018;Wallace & Stevenson, 2014;Zhou et al, 2018), with accumulating evidence showing that this would be a common endophenotype also for other neurodevelopmental disabilities (Wallace & Stevenson, 2014;Zhou et al, 2018). Specifically, individuals with ASD have repeatedly shown an extended temporal binding window (TBW; an epoch of time within which stimuli from different sensory modalities are highly likely to be bound) which would bring to an imprecise temporal processing of sensory stimuli (Zhou et al, 2018).…”
Section: What Are the Lower-level Perceptual Features Linked To Biolosupporting
confidence: 81%
“…Our results suggest that a candidate core mechanism playing a role in BM processing anomalies in ASD is linked to the temporal properties of moving dots embedded in a PLD. This is consistent with several experimental pieces of evidence and theoretical proposals suggesting that one of the core anomaly of individuals with ASD is related to temporal binding of uni-and -multi-sensory information (Brock, Brown, Boucher, & Rippon, 2002;Feldman et al, 2018;Wallace & Stevenson, 2014;Zhou et al, 2018), with accumulating evidence showing that this would be a common endophenotype also for other neurodevelopmental disabilities (Wallace & Stevenson, 2014;Zhou et al, 2018). Specifically, individuals with ASD have repeatedly shown an extended temporal binding window (TBW; an epoch of time within which stimuli from different sensory modalities are highly likely to be bound) which would bring to an imprecise temporal processing of sensory stimuli (Zhou et al, 2018).…”
Section: What Are the Lower-level Perceptual Features Linked To Biolosupporting
confidence: 81%
“…These findings suggest that when processing this real‐world, dynamic stimulus, high‐functioning individuals with ASD were similar to controls in auditory and visual sensory cortical brain areas, as well as in subcortical brain regions (pulvinar and SC) generally reported to integrate auditory and visual information. The lack of a group difference in extracted BOLD values in the present study was not inconsistent with a recent meta‐analysis in that AV integration differences between those with ASD and controls was greater when using linguistic stimuli than with nonlinguistic stimuli [Feldman et al, ], which was explicitly avoided in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…Prior research has demonstrated that individuals with ASD differ from controls when integrating different modalities of sensory inputs for nonnatural stimuli such as basic shapes and pure tones [de Boer‐Schellekens, Keetels, Eussen, & Vroomen, ; Foss‐Feig et al, ] as well as complex natural stimuli such as speech [Megnin et al, ; Stevenson et al, ; Thye et al, ] or static real‐world images [Russo et al, ]. However, these temporal differences can vary depending on the complexity of the stimuli [Feldman et al, ; Noel, De Niear, Stevenson, Alais, & Wallace, ; Stevenson & Wallace, ]. Some studies have investigated multisensory processing in ASD using real‐world, dynamic stimuli: For instance, studies using dynamic stimuli have varied in the duration of stimuli presentation and task demands, including short video clips of a few seconds followed immediately by a forced‐alternative choice task selection [Stevenson et al, ], live images followed by a forced‐alternative choice task [Greenfield et al, ], or passive movie watching with no task [Gabrielsen et al, ; Russo et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is evidence in ASD (especially in children with ASD) of impaired processing of complex information as opposed to unaffected processing of simple information (Bertone, Mottron, Jelenic, & Faubert, 2003;Bertone, Mottron, Jelenic, & Faubert, 2005). This conclusion, however, is challenged by a recent meta-analysis, which suggests, summarizing studies on a variety of audio-visual MSI tasks in ASD, that differences between patients and typically developing individuals increasingly balance out with age (Feldman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%